Classification Techniques in Data Mining - Dukitha, M; Sindhu, R (International Journal of Computer Sciences and Engineering, 2025)
Data mining is a emerging field which has attracted a large number of information , industries due to huge volume of data managed in recent days. Classification techniques to improve business opportunity and to improve the quality of services provided. An classification is one of the most useful and important techniques. Classification techniques are useful to handle large amount of data. Various classification techniques covered in the paper is based on the decision tree. The regression tree based classification J48, CART and ID3.